Cardiovascular morbidity following conventional therapy versus allogeneic hematopoietic stem cell transplantation after childhood, adolescent, and young adult leukemia in Finland. Issue 11 (21st February 2023) - Kero, Andreina E.; Taskinen, Mervi; Volin, Liisa; Löyttyniemi, Eliisa; Itälä‐Remes, Maija; Lähteenmäki, Päivi M.
Abstract: Allogeneic hematopoietic stem cell transplantation (aHSCT) represents a therapeutic choice for high‐risk and relapsed leukemia at a young age. In this retrospective population‐based study, we evaluated cardiovascular complications after aHSCT (N = 272) vs conventional therapy (N = 1098) among patients diagnosed with acute lymphoblastic or acute myeloid leukemia below 35 years between 1985 and 2004. Additionally, siblings from a prior comparison group served as population controls (N = 39 217). Childhood leukemia and aHSCT was associated with a 16‐fold HR for developing arterial hypertension (HR 16.8, 95%CI 1.5‐185.5) compared with conventional therapy. A 2‐fold HR for any cardiovascular complication was observed after AYA leukemia and aHSCT vs conventional treatment (HR 2.7, 95% CI 1.4‐5.1). After AYA leukemia and aHSCT, the HR of cardiac arrhythmia was significantly elevated vs conventional therapy (HR 14.4, 95% CI 1.5‐125.2). Moreover, after aHSCT in childhood, elevated hazard ratios (HRs) were found for cardiomyopathy/ cardiac insufficiency (HR 105.0, 95% CI 10.0‐1100.0), cardiac arrhythmia, and arterial hypertension (HR 20.1, 95%CI 2.5‐159.7 and HR 20.0, 95%CI 4.1‐97.4) compared with healthy controls. After adolescent and young adult (AYA) leukemia and aHSCT, markedly increased HRs were observed for cardiac arrhythmia (HR 29.2, 95%CI 6.6‐129.2), brain vascular thrombosis/ atherosclerosis and cardiomyopathy/cardiac insufficiency (HR 23.4, 95%CI 7.1‐77.4 and HR 19.2, 95%CI 1.5‐245.2) compared with healthy controls. As the cumulative incidence for cardiovascular complications rose during the follow‐up of childhood and AYA leukemia patients, long‐term cardiovascular surveillance is warranted to optimize the quality of life after childhood and AYA leukemia following both conventional treatment and aHSCT. Abstract : What's new? Thus far, only few studies have compared late cardiovascular effects after allogeneic hematopoietic stem cell transplantation (aHSCT) to those after conventional therapy particularly in childhood and young adult ALL and AML patients. Our nationwide study also demonstrated increased hazards for developing late cardiovascular sequelae following both conventional treatment and aHSCT compared to healthy controls. Hence, our results present pivotal information to narrow the knowledge gap on cardiovascular complications also after intensified treatment of childhood and AYA leukemia, and warrant individualized, risk‐based and long‐term cardiovascular medical surveillance.